Chemical and morphological evolution of PA-6/Epm/Epm-g-MA blends in a twin screw extruder - Machado, A. V. (1999)
Chemical conversion and morphological evolution of PA-6/EPM/EPM-g-MA blends along a twin screw extruder were monitored by quickly collecting small samples from the melt at specific barrel locations. The results show that the MA content of all blends decreases drastically in the first zone of the extruder, i.e., upon melting of the blend components. Significant changes in morphology are also observed at this stage. A correlation between chemistry and morphology could thus be established.